Importance of Digitalization and Information System in Business: A Literature Review - Wijayanto, Gatot; Widayati, Tri; Alamsyah, Nur; Aminudin, Rosihan (IJBLE Scientific Publications Community Inc., 2026)
The rapid advancement of digital technologies has fundamentally transformed modern business operations, making digitalization and information systems essential components of organizational success. This study aims to examine the importance of digitalization and information systems in business through a comprehensive literature review. Using a qualitative research approach, relevant academic articles, books, and conference proceedings were analyzed to identify key themes related to business performance, decision-making, competitive advantage, and implementation challenges. The findings reveal that digitalization significantly enhances operational efficiency, productivity, and customer responsiveness, while information systems such as management information systems, decision support systems, and enterprise resource planning systems play a crucial role in supporting data-driven decision-making and organizational integration. Additionally, the review highlights that digitalization contributes to innovation and sustained competitive advantage when aligned with organizational capabilities and strategic objectives. However, challenges including high implementation costs, skills gaps, cybersecurity risks, and resistance to change remain significant barriers, particularly for small and medium-sized enterprises. This study contributes to the existing body of knowledge by synthesizing fragmented literature and providing a holistic understanding of the strategic importance of digitalization and information systems in business. The findings offer valuable insights for researchers, practitioners, and policymakers seeking to navigate digital transformation effectively.